A new species of the spider genus Wirada (Araneae, Theridiidae) from Mexico, with taxonomic notes on the genus and a key to the species - Campuzano, Emmanuel F.; Ibarra-Núñez, Guillermo (Zootaxa, 2018)
Wirada Keyserling, 1886 is one of the smallest genera of Theridiidae with only five South American species (World Spider Catalog 2018). Keyserling (1886) described first Wirada punctata (male) from Peru. Simon (1895) described W. rugithorax and W. tovarensis (males) from Venezuela, but Levi (1963) synonymized W. rugithorax with W. punctata. Later, Levi (1967) described W. tijuca (male) from southeastern Brazil, and lately Lise et al. (2009) described W. sigillata Lise, Silva & Bertocello, 2009 and W. araucaria Lise, Silva & Bertocello, 2009 (males and females) from southern Brazil. Simon (1894) placed Wirada in its group Histogonieae, and stated it is close to Pholcommateae. Until now, none species of Wirada has been included in any phylogenetic study of Theridiidae, only Agnarsson (2004) when commented the Pholcommatinae said “Based on the synapomorphies of the group it is likely that ... Wirada belong to this subfamily.” Recently, this genus was reported (as Wirada sp1) from two localities in Mexico (Ibarra et al. 2011; Álvarez-Padilla 2015; Rivera-Quiroz et al. 2016) and subsequent samplings on three other sites from Chiapas (Campuzano et al. 2016) exposed more specimens. After examining these specimens, we found they do not match any of the known species and therefore we propose a new species. We also include taxonomic and biological notes about the genus and a key to the species.